Konsumen Dan Transportasi Bus: Studi Terhadap Perlindungan Hukum Bagi Penumpang Bus Di Kota Surakarta - Setiawan, Ricky, Kelik Wardiono, S.H., M.H, Inayah, S.H., M.H (2015)
Transportation is an important sub system to support economic of a country. Definitively transportation is goods and human movement from one place to another place using motor vehicles. By transportation facility people and goods will move easily and faster from one area to another area. Surakarta is city with traffic rute which passed by bus transportation from West Java and East Java. P.O Mulyo Indah and Perum Damri ar e two autobus companies which are based in Surakarta which give safe, comfortable, tidy, fluent and solid as the transportation purposes. As matter of fact there are still many of lacks need to be fixed by many bussinessman of autobus companies, and passangers as the consumers who use the transportation facilities feel are not comfortable to use both autobus companies because often the bus full of passangers and don't pay attention of standard minimum services to factor of comfortably passangers. Based on Undang-Undang Nomor 8 Tahun 1999 regarding to Consumers Protection and Undang-Undang Nomor 22 Tahun 2009 regarding to Traffic and Land Transportation also other rules regarding to the consumers rights and obligations of businessman in runing their business. There are so many things have to be fixed by both autobus companies to fulfill minimum of standards transportation service to passangers.